Helicobacter pylori Eradication Therapy-associated Diarrhea - Hoon Gil Jo; Yong Sung Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2021)
Eradication of Helicobacter pylori has contributed to the treatment of peptic ulcers and mucosa-associated lymphoid tissue lymphoma. Moreover, it has possibly decreased the prevalence of gastric cancer. However, eradication therapy is associated with various adverse effects, of which diarrhea is the most common. The incidence of diarrhea after eradication treatment varies from 8% to 48%. In particular, the incidence is higher in patients who receive first-line standard triple therapy compared with those who receive second-line therapy. Both antibiotics and proton pump inhibitors, components of eradication therapy, have short-term and long-term impacts on gut microbiota. The alterations of gut microbiota may not recover until 1 year after eradication therapy. Most cases of diarrhea that occur after eradication therapy are antibiotic-associated diarrhea caused by the destruction of the normal gut microbiota. In some cases, Clostridioides difficile-associated diarrhea occurs after eradication therapy. If bloody diarrhea occurs after eradication therapy and the Clostridioides difficile toxin is not detected, antibiotic-associated hemorrhagic colitis associated with Klebsiella oxytoca infection should be suspected. It is crucial to explain the possibility of diarrhea before initiating eradication therapy to increase compliance. Furthermore, probiotics may be administered to reduce diarrhea. If severe diarrhea or symptoms other than the usual antibiotic-associated diarrhea occur during or after eradication therapy, antibiotics should be discontinued. In addition, appropriate tests to determine the cause of diarrhea should be performed. This review summarizes the alteration of the gut microbiota, the causes of diarrhea after Helicobacter pylori eradication therapy, and its management.